PENGARUH MEDIA FLIPPITY TERHADAP KEMAMPUAN MENULIS PUISI PADA SISWA KELAS X SMA NEGERI 4 TEBING TINGGI TAHUN AJARAN 2022/2023 - Bintang Immanuella Sidabuke; Elly Prihasti Wuriyani (Yayasan Nusantara Hasana Berdikari, 2023)
This study aims to describe the effect of using flippity media on the ability to write poetry. The population of this study were all class X students of SMA Negeri 4 Tebing Tinggi for the 2022/2023 academic year. The sample for this study was class X-1, which consisted of 34 people using the cluster sampling technique. In this study the experimental class was given a poetry writing ability test before and after using flippity media. The conclusion of this study is that the average value of the students' pretest was 51.76. And the average value of the students' posttest was 85.41. The ability to write poetry in class X students of SMA Negeri 4 Tebing Tinggi for the 2022/2023 school year after using media flippity has a significant effect. This is proven through hypothesis testing, namely tcount > ttable (14.88 > 2.03). So that in this study H0 was rejected and Ha was accepted. So, it can be concluded that media flippity has an effect on improving students' ability to write poetry.